‘Making it or Breaking it’ in Iceland: An Exploration of Expatriate Spouses’ Adaptation Strategies and Experiences - Stimming, Cynthia Ulrike, 1978- (2012)
Expatriate spouses play a vital role in the decision to quit or pursue an assignment overseas. This study is an exploration of the experiences, themes and dilemmas affecting spouses in Iceland. Iceland’s tumultuous weather, its people’s ‘herd’ mentality and the company’s interdependent relationship with the spouses all combine in a heady recipe resulting in ‘Making it or Breaking it’ in Iceland. The social reality of migration and its effects are explored; if the expatriate spouses’ migration adaptation strategies and experiences can be regarded as transformative, then migration can be seen as evolutionary and not corrosive. Loneliness and ecstasy, to satisfaction and acceptance is the migrant’s story, sorely testing their resilience and the very fabric of their identity. Key words : expatriate, spouse, migration, adaptation, strategies, transformative, resilience, Iceland, assignment, overseas, company, migrant, identity, “making it”, “breaking it”. Makar erlendra starfsmanna spila stórt hlutverk í ákvörðunum um að takast á við verkefni fjarri heimahögum og ákvörðunina um að ljúka þeim. Þessi rannsókn er könnun á þeirri reynslu og þeim erfiðleikum sem hafa áhrif á maka erlendra starfsmanna íslenskra fyrirtækja. Þessi rannsókn lítur á það hvernig erfitt veðurfar, “hjarðhegðun” íbúanna og samband fyrirtækjanna við makana veldur því að útkoman er ‘Making it or Breaking it’ á Íslandi. Litið er á hvernig búferlaflutninga geti verið bæði vandamál og tækifæri til þróunar fyrir einstaklinga. Saga innflytjandans einkennist af einmanaleiki og gleði, til sátta og fullnægingar, það er saga innflytjandas, sem reynir bæði á þol maka erlendra starfsmanna og á sjálfsmynd þeirra. To gain access to this document please contact Cynthia Stimming at moonstone_13@yahoo.com